2022
DOI: 10.1111/his.14667
|View full text |Cite
|
Sign up to set email alerts
|

Morphological spectrum and molecular features of somatic malignant transformation in germ cell tumours

Abstract: Aims Somatic malignant transformation (SMT) arising in germ cell tumours (GCTs) is an infrequent, but clinically relevant event. There is only limited knowledge on the morphological spectrum of SMT, and the therapeutic management of these patients is poorly defined. In this work we revisit two consecutive case series (n = 756) of GCTs. Clinicopathological data of SMTs arising in GCTs were determined, with a focus on the histopathological spectrum, and molecular aspects were obtained by Fluorescence in situ Hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…9,10 While there is a wide array of possible malignant transformations, adenocarcinoma, neuroectodermal, and rhabdomyosarcoma are more commonly seen (with mesodermal differentiation being the most common). 9,11,12 Histology is essential in making the diagnosis. In ENET, an overgrowth of immature elements is seen, manifesting as neuroepithelium that may form rosette-like tubular structures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,10 While there is a wide array of possible malignant transformations, adenocarcinoma, neuroectodermal, and rhabdomyosarcoma are more commonly seen (with mesodermal differentiation being the most common). 9,11,12 Histology is essential in making the diagnosis. In ENET, an overgrowth of immature elements is seen, manifesting as neuroepithelium that may form rosette-like tubular structures.…”
Section: Discussionmentioning
confidence: 99%
“…3 Regarding malignant transformation, it has been suggested that there is a progenitor cell located within initial teratoma which then gives rise to the malignant neoplasm. 9,13 Notably, many of these malignant transformations of these testicular germ cell tumors contain 12p gains and may affect genes on this chromosome, notably the oncogene KRAS. 9,13 While this may provide a molecular target for therapy, the mainstay of treatment remains resection and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations